WONDERWORLD OF THE MICROBIOME - Adrian Balanean (Amaltea Medical Publishing House, 2019)
Dear Readers, For healthy development and growth in childhood, the intestinal flora, or microbiome, plays a key role. The particular makeup of breast milk provides the optimum nutrition for the newly born child and a support for the microbiome. This contains an abundance of positive substances. Current interest has been focusing on the so-called human milk oligosaccharides (HMO) as a centre of particular attention, which represents an essential part of the content of breast milk. The importance of these components has already been known to researchers for some time, but it has not been possible until recently to enrich infant formulae with selected and particularly important HMOs. These HMOs are the same as those found in breast milk. They have been positively evaluated both in Europe and in the United States ("Novel Food" status by the EFSA, GRAS status by the FDA). The first results of these studies look very promising. Learn more about this exciting topic on the following pages!